2020
DOI: 10.1186/s12936-020-03328-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum histidine-rich protein 2 diversity in Ghana

Abstract: Background: In the absence of microscopy, Plasmodium falciparum histidine-rich proteins 2 (PfHRP2)-based rapid diagnostic tests (RDTs) are recommended for the diagnosis of falciparum malaria, particularly in endemic regions. However, genetic variability of the pfhrp2 gene threatens the usefulness of the test due to its impact on RDT sensitivity. This study aimed to investigate the diversity of pfhrp2 in malaria cases among children in Ghana. Methods: A cross-sectional study was conducted at the Adidome Governm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
20
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 36 publications
15
20
4
Order By: Relevance
“…On the contrary, PfHRP2 repeat types obtained within this study showed certain difference from African and global reports in a number of ways. First, PfHRP2 type 12 repeat was found in a few isolates (10.5%) this did not align with previous studies from Kenya [30], Ghana [31]and central America [36]. However, studies from Senegal [34] showed the presence of type 12 repeats in a few isolates similar to the present study.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…On the contrary, PfHRP2 repeat types obtained within this study showed certain difference from African and global reports in a number of ways. First, PfHRP2 type 12 repeat was found in a few isolates (10.5%) this did not align with previous studies from Kenya [30], Ghana [31]and central America [36]. However, studies from Senegal [34] showed the presence of type 12 repeats in a few isolates similar to the present study.…”
Section: Discussioncontrasting
confidence: 94%
“…The ndings of PfHRP3 repeat types in the present study are consistent with previous reports from Kenya [30], Yemen [29], Ghana [31], and globally [8]. On the other hand, type 2 repeat was absent in all isolates of PfHRP3 sequence in Ethiopia as well as other parts of Africa [29][30][31], but type 2 repeat has been reported in PfHRP3 in few isolates from Kenya [30] and India [32]. This variation observed in PfHRP2 and PfHRP3 repeat types might be due to differences in geographical and transmission settings [8,38,39], frequency of exposure of drug and level of immunity of study participants [40,41], clinical versus asymptomatic study participants, and methods used for molecular analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite recent advances in genome sequencing of malaria parasites, microsatellite markers remain an important source of data to understand the genetic diversity and relatedness of parasite populations and understanding of transmission dynamics [ 15 , 21 , 22 , 32 , 33 , 48 51 ]. In this study, the genetic relatedness among monoclonal Ugandan parasites and between monoclonal Ugandan and Eritrean parasites was investigated using 7-microsatellite-marker haplotypes.…”
Section: Discussionmentioning
confidence: 99%